The Story of the Olympics - Lacey, Minna; Francis, Neil; Kelly, Alison; Lawrence, Michelle; Mounter, Paddy (London Usborne, 2012)
From a festival in ancient Greece to a worldwide event today, the Olymics have inspired athletes and supporters alike. Find out how the biggest sports event in the world was born and discover the amazing heroes who made Olympic history
Arts (Sports)
Keywords: Sports and Games